1991
DOI: 10.1111/j.1365-2818.1991.tb03103.x
|View full text |Cite
|
Sign up to set email alerts
|

Direct visualization of colloidal gold‐bound molecules and a cell‐surface receptor by ultrahigh‐resolution scanning electron microscopy

Abstract: SUMMARY The structure of protein A‐coated colloidal gold particles, and of macrophage cell‐surface receptors conjugated with immunogold particles, was studied using an ultrahigh‐resolution scanning electron microscope. Protein A, when conjugated with 15‐nm gold, formed a coat completely surrounding the particle. Particles conjugated with both protein A and immunoglobulin G (IgG) were similar, but with additional protrusions formed by the IgG. IgG molecules directly bound to gold were resolved sometimes as comp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
5
0

Year Published

1991
1991
2014
2014

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 11 publications
(5 citation statements)
references
References 11 publications
0
5
0
Order By: Relevance
“…A recent study demonstrated the SEM examination of uncoated biological specimens, using the plasma-ion shower method for which resolution in the nanometer range was obtained (10). Single colloidal gold-bound molecules have been directly visualised by ultra-high-resolution SEM using staining with Osmium by the OTO method (11,12). Compared with these studies, our approach employs commonly used instrumentation and not staining procedures that affect the shape of the sample.…”
Section: Discussionmentioning
confidence: 99%
“…A recent study demonstrated the SEM examination of uncoated biological specimens, using the plasma-ion shower method for which resolution in the nanometer range was obtained (10). Single colloidal gold-bound molecules have been directly visualised by ultra-high-resolution SEM using staining with Osmium by the OTO method (11,12). Compared with these studies, our approach employs commonly used instrumentation and not staining procedures that affect the shape of the sample.…”
Section: Discussionmentioning
confidence: 99%
“…Therefore, we prefer the CC plates to another substrate for our observations. Spreading molecules on CC plates (Tanaka et al, 1989(Tanaka et al, , 1991 allows some molecules to be observed without charging effects, but is not generally applicable. We have therefore taken the approach of using a solution as a source of impregnating or staining metal, to decrease charging and improve the electron yield.…”
Section: Discussionmentioning
confidence: 99%
“…In this way, information about the receptor's distribution can be obtained indirectly by imaging the receptor-antibody immune complex, and the characterization and orientation of the receptor can be seen indirectly. The receptor distribution on the cell membrane surface can then be depicted visually, and quantitative analysis of the number of receptors can be carried out (Tanaka et al 1991). In this study we used AFM at a nanometer scale to investigate the distribution of VEGFR-2 with immune complex labeling and to determine its receptor density on the glioma microvascular endothelial cell surface.…”
Section: Introductionmentioning
confidence: 99%